ANALISIS KEPUASAN KONSUMEN BERBASIS IMPORTANCE PERFORMANCE ANALYSIS (IPA) PADA GERAI RITEL ALFAMART DI KOTA DENPASAR - Ni Made Dwi Ratna Cahyanti; Desak Made Ramya Pranihita Sukma; Komang Prasetya Wahyu Nugraha; I Gusti Ayu Ketut Giantari (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
the purpose of this study is to find out how big the gap is from the level of consumer interest and service performance of Alfamart in Denpasar City. This research uses descriptive research with a quantitative approach. The sampling method that will be used in this study is non- probability with purposive sampling technique. The number of respondents who filled out the survey was 104 individuals who met the sample criteria to be used. The data analysis technique used is the Importance Performance Analysis (IPA) method which shows the relationship between the level of importance and the level of performance. The correlation of each item to the total score of each statement for variables/attributes Tangible, Responsiveness, Reliability, Assurance, Empathy, all yields an r-table above 0.361 with a significance value of 0.06 (6 persen). Thus, the entire statement of research variable items is valid and reliable. This means that overall all indicators that are considered important are in accordance with customer expectations so that there is no need to prioritize a particular indicator. Suggestions that can be given to Alfamart retail outlets in Denpasar City Alfamart retail outlets in Denpasar City must maintain the attributes that are located in Quadrant II so that consumers still feel satisfied